Patterns of Utilization of Maternal Healthcare Services in Haryana, India - Sonal Katyal (ACHSM, 2018)
Background: Despite being a relatively smaller state, Haryana's per capita Gross State Domestic Product (GSDP) is high. The statistical data on the status of women has a different story to share.  Objective: This study analyzes the maternal healthcare situation in Haryana to examine the differential in utilization of maternal health care service i.e. antenatal care on the basis of socio economic and socio demographic indicators such as Women's age at Birth, Birth order, Education, Residence, Religion, Wealth index and Caste.  Methodology: The present study uses the third round of the National Family Health Survey (NFHS) data which is similar to the Demographic and Health Surveys (DHS). DHS collects, disseminates national data on health and population in developing countries.  Findings: Indicate that economic status, husband's education and caste have effect on the utilization of antenatal care services.  Conclusion: The present study demonstrates several socio economic and demographic factors affecting the utilization of antenatal care services in Haryana. Efforts need to be taken at community and household level to improve utilization.  Abbreviations: NFHS- National Family Health Survey; DHS- Demographic and Health Surveys; MDG- Millennium Development Goals; SC/ST-Scheduled caste/Scheduled tribe; WHO-World Health Organization; MOHFW- Ministry of Health and Family Welfare; ANM - Auxiliary Nurse Midwife; VIF - Variance Inflation Factor; OBC- Other Backward Classes; ANC- Antenatal Care; TBA - Trained Birth Attendant